Design, synthesis and in vitro α-glucosidase inhibition of novel coumarin-pyridines as potent antidiabetic agents. (28th September 2018) - Adib, Mehdi; Peytam, Fariba; Rahmanian-Jazi, Mahmoud; Mohammadi-Khanaposhtani, Maryam; Mahernia, Shabnam; Bijanzadeh, Hamid Reza; Jahani, Mehdi; Imanparast, Somaye; Faramarzi, Mohammad Ali; Mahdavi, Mohammad; Larijani, Bagher
Abstract : Herein, novel coumarin-pyridine derivatives4a–p as potent α-glucosidase inhibitors were synthesized by a one-pot and three-component synthesis method. Abstract : In this work, we report an efficient, one-pot and three-component synthesis of novel coumarin fused pyridine derivatives4a–p . Heating the mixture of 4-hydroxycoumarins and ammonium acetate in DMF gave the corresponding 4-aminocoumarins, which subsequently went through Michael addition–cyclocondensation with α-azidochalcone derivatives to produce our desired products in high yields. The synthesized compounds4a–p were evaluated for α-glucosidase inhibitory activity and all of them exhibited excellent in vitro yeast α-glucosidase inhibition with IC50 values ranging from 101.0 ± 2.0 to 227.3 ± 1.4 μM when compared with the standard drug acarbose (IC50 = 750.0 ± 1.5 μM). A kinetic study of the most potent compound4i revealed that it inhibited α-glucosidase in a competitive mode. A docking study of the most active compounds4i, 4h, and4j was also performed.